G167(P) Chest pain in children is rarely cardiac. does ecg help?. (27th April 2015) - Babu, P; Dickson, S; Dhar, D; Hapuarachchi, D; Murtagh, K; Damda, F
Abstract : Aims: Chest pain is a common reason for presentation to the children's emergency department (ED). It is known that chest pain in children, compared to adults, is much less likely to be caused by cardiovascular disease. Electrocardiographs (ECGs) are cheap, fast and readily available. When interpreted appropriately they can be useful in demonstrating cardiac causes of chest pain. We aimed firstly to determine the incidence and likely causes of paediatric chest pain presenting to our busy Children's ED and secondly to analyse the usefulness of ECGs in this cohort. Methods: We retrospectively analysed the ED case notes of all children (aged under 16 years) presenting with chest pain over a 4 year period (April 2009 to March 2013) to a busy Children's ED in an urban district general hospital. Results: 1126 attendances presented with chest pain, approximately 1% of all attendances over four years. Of those with chest pain 54% were male and the modal age of presentation was 12 years. Based on history and clinical examination the commonest cause attributed to chest pain was musculoskeletal. Only 1% of cases had a possible cardiac aetiology; 1 patient had pericarditis, 1 patient had myocarditis, 2 patients had a pre-existing cardiac condition, 3 patients had arrhythmias and 8 were under investigation for recurrent palpitations. Thirty per cent of patients with chest pain had an ECG carried out. Patients with cardiovascular, psychiatric and musculoskeletal diagnoses were most likely to have had an ECG done. The majority of ECGs were normal (91%). The commonest abnormality was high take off/mild ST elevation, with only 10% of such patients having cardiac enzymes requested. Some of the ECG abnormalities identified could not be attributed to chest pain. Conclusion: Incidence of chest pain presenting to our ED was 1%. The commonest recorded cause was musculoskeletal. Fewer than 1% had a possible cardiac aetiology for chest pain. ECG is a useful test for children presenting with chest pain. Very few patients with mild ST elevation had cardiac enzyme levels checked.